1, 8-Naphthyridinic fluorescent 'turn-on' and 'turn-off' chemosensors for detection of F− and Hg2+ ions mimicking INHIBIT molecular logic behaviour1. Issue 11 (7th June 2015) - Chahal, Mandeep K.; Sankar, Muniappan
<x xml:space="preserve">Abstract</x> Naphthyridine-based fluorescent chemosensors were prepared. They exhibited a selective dual-channel response to detect F− and Hg2+ ions with lower detection limits (0.5–2 ppm range).